EFEKTIVITAS KOMUNIKASI WHATSAPP SEBAGAI MEDIA PENUNJANG PEKERJAAN KARYAWAN UNIS PADA MASA PANDEMI COVID19 - Pradesti, Ajeng; Salsabil, Luna Safitri (Universitas Islam Syekh Yusuf, 2022)
The COVID-19 pandemic requires employees in an office to work from home, which is called Work Form Home (WFH). Causing employees to communicate through application mediums, one of which is Whatsapp. The purpose of this study was to determine the Effectiveness of Whatsapp Communication as a Media Supporting the Work of Unis Employees During the Covid19 Pandemic. research method using descriptive quantitative. The results of research on the effectiveness of Whatsapp Communication as a Supporting Media for Unis Employee Work during the Covid19 Pandemic were considered effective.